2012
DOI: 10.1248/bpb.b12-00343
|View full text |Cite
|
Sign up to set email alerts
|

Menthosomes, Novel Ultradeformable Vesicles for Transdermal Drug Delivery: Optimization and Characterization

Abstract: Menthosomes, novel deformable carriers for the enhancement of transdermal delivery are introduced in this study. Meloxicam (MX)-loaded menthosomes were formulated, and their physicochemical characteristics and skin permeability were evaluated. A two-factor spherical and second-order composite experimental design was used to prepare the formulation of the menthosomes. Ten formulations of menthosomes composed of a phospholipid as the lipid bilayer carrier, cholesterol (Chol) as a stabilizer and cetylpyridinium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…12) As shown in Table 1, MX loaded vesicles (menthosomes, transfersomes and liposomes) composed of a controlled amount of MX, PC, and various amounts of Chol as membrane stabilizer, and CPC and MEN as penetration enhancer were prepared. l-menthol was reported to improve the skin permeation of various drugs by increase of drug partition and diffusion.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…12) As shown in Table 1, MX loaded vesicles (menthosomes, transfersomes and liposomes) composed of a controlled amount of MX, PC, and various amounts of Chol as membrane stabilizer, and CPC and MEN as penetration enhancer were prepared. l-menthol was reported to improve the skin permeation of various drugs by increase of drug partition and diffusion.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent approaches in vesicular modulating drug delivery through skin have resulted in many designs of novel vesicular carriers e.g., deformable liposomes (transfersomes), 7) niosomes, 8) ethosomes, 9) invasomes, 10) flexosomes 11) and menthosomes. 12) Transfersomes are the first generation of elastic vesicles introduced by Cevc and Blune 7) and consist mainly of phospholipids and an edge activator or a single-chain surfactant which having a high radius of curvature that increases deformability of the bilayers. 13) Niosomes are the second generation of elastic vesicles introduced by van den Bergh et al 8) and compose of the optimal ration of non-ionic surfactant and cholesterol.…”
Section: Hcl)mentioning
confidence: 99%
See 2 more Smart Citations
“…70,87 Table 5 summarizes a review of several drugs reported for transdermal delivery using ELs and recently reported new ELs. [88][89][90][91][92][93][94][95][96][97][98] Furthermore, these latest ELs were tabulated (Table 6) with valuable information, such as definition, composition, classification, advantages, and inherent limitations. 14 …”
Section: Local Anesthetic Drugsmentioning
confidence: 99%